Family functioning, social support and quality of life among elderly in the Public Health Center III South Denpasar - Dewianti; Kadek Tresna Adhi; R.A. Tuty Kuswardhani (Public Health and Preventive Medicine Archive, 2013)
The elderly population has increased alongside with the increasing of life expectancy in elderly. Unfortunately, this is not followed by increased quality of life among elderly. Interview with 10 elderly at the Public Health Center III South Denpasar revealed that they experienced loneliness and felt neglected which affect their quality of life. This study aims to determine the relationship between family functioning, social supports (friends, family and community) and quality of life of elderly at the Public Health Center III South Denpasar in 2013. This study is a cross-sectional, involving 125 elderly who still have a partner and was selected using systematic random sampling method. Agreed participants were interviewed to obtain data related to family function, social support (partner, family and community) as well as their quality of life. Data were analysed using univariate, bivariate and multivariate. Statistical testing used were chi-square test and logistic regression. The study revealed that most of the elderly has a low quality of life (62.4%), a low family functioning (72%), lack of family support (54.4%) and lack of community support (67.2%); however, most of them has a high support from their partner (54.4%). The chi square test result showed that function of family, social support (friends, family, and community) were significantly associated with quality of life in elderly (p<0.05). Results of logistic regression showed that function of family has a significant relation with quality of life in elderly (p<0.05). It can be concluded that better family functioning improves the quality of life in elderly.